Supply chain management: managing intellectual property - Prokop, Darren (Henry Stewart Talks, 2022)
Intellectual property rights, Patent, Trademark, Copyrights, Trademark protection, Domains, Parallel imports, Supply chain management, Art law, Fashion law, World Trade Organization